2015
DOI: 10.1038/onc.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

YAP forms autocrine loops with the ERBB pathway to regulate ovarian cancer initiation and progression

Abstract: Mechanisms underlying ovarian cancer initiation and progression are unclear. Herein, we report that the Yes-associated protein (YAP), a major effector of the Hippo tumor suppressor pathway, interacts with ERBB signaling pathways to regulate the initiation and progression of ovarian cancer. Immunohistochemistry studies indicate that YAP expression is associated with poor clinical outcomes in patients. Overexpression or constitutive activation of YAP leads to transformation and tumorigenesis in human ovarian sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 45 publications
8
99
1
Order By: Relevance
“…This raised the possibility of the existence of a feedforward loop between these two pathways. Indeed, an autocrine loop between the Hippo signaling pathway and a receptor tyrosine kinase pathway (ERRB) has been described recently in ovarian cancer cells (43). We confirmed the presence of an autocrine, feed-forward pathway between the oncogenic Hippo signaling pathway and FGFR pathway by adding FGF5 to a CCA cell line with virtually no basal YAP immunoreactivity and observed a marked increase in YAP expression.…”
Section: Discussionsupporting
confidence: 71%
“…This raised the possibility of the existence of a feedforward loop between these two pathways. Indeed, an autocrine loop between the Hippo signaling pathway and a receptor tyrosine kinase pathway (ERRB) has been described recently in ovarian cancer cells (43). We confirmed the presence of an autocrine, feed-forward pathway between the oncogenic Hippo signaling pathway and FGFR pathway by adding FGF5 to a CCA cell line with virtually no basal YAP immunoreactivity and observed a marked increase in YAP expression.…”
Section: Discussionsupporting
confidence: 71%
“…A research group found that YAP plays an important role in regulating ovarian adult granulosa cell tumor cell proliferation, migration, and steroidogenesis 25. They also found that YAP interacts with epidermal growth factor receptor signaling pathway to regulate growth of ovarian surface epithelial cells and OC cells 26. Most recently, the same group came to a conclusion that YAP may be involved in the initiation and progression of fallopian tube epithelia-derived cancer 27.…”
Section: Discussionmentioning
confidence: 99%
“…Such relationship between YAP1 and the EGFR pathway was found to be important in the progression of oesophageal cancer in patients treated with EGFR inhibitors [61]. Recently published results of knockdown of YAP1 and knockdown of ERBB3 study suggested presence of an autocrine loop between YAP1 and EGFR which may control ovarian cell tumourigenesis and cancer progression [63].…”
Section: Hippo Upregulates Egfr/kras Pathwaymentioning
confidence: 99%
“…Recent reports [50,[61][62][63] revealed that the Hippo pathway effector, YAP1 protein, is involved in the regulation of EGFR/KRAS signalling ( Figure 3). During homeostasis, degradation of YAP1 is triggered by ubiquitin ligase complex substrate recognition factors SOCS5/6.…”
Section: Hippo Upregulates Egfr/kras Pathwaymentioning
confidence: 99%